PENGARUH WORD OF MOUTH, BRAND IMAGE DAN BRAND AWARENESS TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH KOTA SEMARANG - Ester Pradina Salaka; Wahyu Hidayat (Universitas Diponegoro, 2019)
Cosmetics today have become one of the most important thing for every woman needs to make their appearance looks more beautiful and interesting. This become a reason why the growth of industrial cosmetics in Indonesia is growing fast, and one of them is Wardah Cosmetic. Wardah is one of Indonesia's local and halal cosmetic brand and has distributed the products around Indonesia including Semarang. This study aims to determine the effect of word of mouth, brand image and brand awareness on purchase decision of Wardah’s cosmetic. The type of the research is explanatory research and the sampling use nonprobability sampling techniques, and purposive sampling method. Data collection using questionnaires and google form. The sample is used amount 100 respondents using Wardah’s products in Semarang City. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test and F test. The result of the study shows that the variables of word of mouth, brand image and brand awarness have an effect on purchase decisions. The variable correlation coefficient of word of mouth, brand image and brand awareness on purchase decisions have a very strong enough relation, and if the variables of word of mouth, brand image and brand awareness have increased or decreased it will make a greatly affect on the purchase decision variable. Based on these results, Wardah is advised to improve quality by adding variety of products according to the needs of female consumers in Indonesia so that consumers are satisfied, making logo designs and packaging colors more interesting and more often do a promotion products in various media, making product displays in the cosmetic outlets and have more interesting advertisements on television so it can encourage purchasing decisions among consumers.